Kritik Desain Bangunan Dalam Novel Born From A Wish Karya Mertha Sanjaya - Riris Saniyati; Wastari Latifah Tyas R.; Eva Dwi Kurniawan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This research examines the architectural side of the novel Born From A Wish by Mertha Sanjaya. The aim of this research is to present the results of criticism of the building designs contained in the novel. The method used is a qualitative method with a descriptive approach. From this research, conclusions were drawn in the form of aesthetic aspects, lighting and furniture arrangement in a building as contained in the excerpt from the novel Born From A Wish by Mertha Sanjaya.